The dissemination via translations of Herbert Spencer's Liberalism in the Hispanic context - Ramírez-Arlandi, Juan (Universidad de La Laguna, 2024)
This study examines the dissemination of English Liberalism, as expounded by Herbert Spencer in The Man versus the State (1884), by analysing various Spanish translations published in Spain and Hispanic America between 1885 and 2019. In terms of methodology, this analysis draws on (i) the assumptions of Descriptive Translation Studies and Cultural Translation Studies; (ii) Lépinette’s (1997) approach to translation history, which combines the socio-cultural with the descriptive-contrastive approaches; and (iii) Toury’s (1995) normative-descriptive model. To that end, an in-depth study of the various translations is first presented to identify the initial and preliminary norms, paying particular attention to the profile of translators, publishers, and paratexts, followed by an analysis of the operational and linguistic-textual norms. It is concluded that the dissemination of liberal political thought in The Man versus the State was influenced by the intricate network of language and text, encompassing intertextuality across the multitude of Spanish translations that emerged between 1885 and 2019 and by the agents and paratexts contextualising these versions.
Keywords: Spencer, Herbert - Crítica e interpretación; History of translation; Norms; Paratexts; Book history; Liberalism